Online Learning Conveniences from Students Perception: A Case Study in Universiti Malaysia Sabah (Global Journal of Human-Social Science, 2014)
Convenience is one aspect that should be considered in an online learning environment. Without convenience it is very impossible to implement successfully online learning particularly in higher learning institution. The purpose of this study was to explore the online learning conveniences from students' perception. A cohort of 61 science physics students from School of Science and Technology (SST) and 41pre-service science teachers from the School of Education and Social Development (SESD) of Universiti Malaysia Sabah, Malaysia comprised the sample. The course involved was Modern Physics and this course is a compulsory. Both groups were supported via an online learning environment, which acted as the main medium for learning. Participants' perception on conveniences was recorded through an open-ended questionnaire and a focus group interview. The output of these qualitativedata, can be categorised into several themes, as in general they felt that learning through online is really convenient and ease; and they were also using online to search for information. Somehow there was also negative feedbackwhere they felt not satisfied with the Internet coverage. In additional the SESD's student stressed that their communication skills were enhanced.
Keywords: problem-based learning; online learning; students’ convenience